Proposed Procedures for Developing Managerial Performance of the Faculties of Al-Azhar University in The Light of Strategic Flexibility Approach - Mohamed Ahmed Gharib Alsaid Hewehy (Deanship of Scientific Research (DSR), the University of Jordan, 2022)
Objectives: The study aimed to present proposed procedures for developing the managerial performance of Al-Azhar University faculties in light of strategic flexibility approach (strategic sensitivity, clarity of vision, core capabilities, selection of strategic goals, joint responsibility, and responsiveness) by recognizing the degree of the importance of practicing its dimensions from the faculty members viewpoint, and calculating the statistically significant differences among the sample members about the degree of importance of their practice, attributed to the study variables (scientific degree - college nature - college headquarters or branch). Methods: The study used the descriptive method, and a questionnaire consisting of (36) items, which was applied to a sample of (587) faculty members at the university to collect data. Results: The study concluded with the agreement of the sample members on the importance of practicing the dimensions of strategic flexibility for the development of managerial performance at Al-Azhar University faculties with a degree of "very important" and with a mean of (4.44), there are no statistically significant differences at the level (0.05) attributed to the study variables (scientific degree- the college nature- The college headquarters or branch), and the study presented proposed procedures to develop the institutional performance at Al-Azhar University. Conclusions: The study recommended the importance of adopting the proposed procedures to develop managerial performance through the application of the dimensions of strategic flexibility at Al-Azhar University and in other Egyptian universities, due to the similarity of structures and systems in these universities, and the importance of the university's administrative, financial and academic independence so that it is able to adapt to various variables, and to attract qualified scientific and administrative staff.